2022
DOI: 10.1021/acs.analchem.1c05098
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Intelligent Cancer Diagnosis Method: 2D Raman Figures Combined with Deep Learning

Abstract: Raman spectroscopy, as a label-free detection technology, has been widely used in tumor diagnosis. However, most tumor diagnosis procedures utilize multivariate statistical analysis methods for classification, which poses a major bottleneck toward achieving high accuracy. Here, we propose a concept called the two-dimensional (2D) Raman figure combined with convolutional neural network (CNN) to improve the accuracy. Twodimensional Raman figures can be obtained from four transformation methods: spectral recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, surface-enhanced Raman scattering (SERS), spatially offset Raman spectroscopy (SORS), and incorporating machine learning are complementary technologies that increase the detection sensitivity in liquid biopsies [63][64][65] and deep layers of tissues and organs [58,66]. They also increase accuracy in discriminant analysis [67][68][69][70][71][72].…”
Section: Technical Breakthroughs Toward Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, surface-enhanced Raman scattering (SERS), spatially offset Raman spectroscopy (SORS), and incorporating machine learning are complementary technologies that increase the detection sensitivity in liquid biopsies [63][64][65] and deep layers of tissues and organs [58,66]. They also increase accuracy in discriminant analysis [67][68][69][70][71][72].…”
Section: Technical Breakthroughs Toward Biomedical Applicationsmentioning
confidence: 99%
“…The literature involving Raman spectroscopy and human diseases is too numerous to list so representative articles are selectively cited here (Table 1). For the early detection and prediction of human disease, applications range from the discriminant analysis of cancer cells [72,94], tissues [51,53,62,69,71,[95][96][97], and serum sample [67,98] to diagnostic procedures via endoscopy [95]. Cheng et al demonstrated that four leukocyte types (granulocytes, monocytes, B cells, and T cells) from healthy people were characterized as a reference of normal hematopoiesis and were distinguished from each other by generating an orthogonal partial least squares discriminant analysis (OPLS-DA) model for the further analysis of leukemic granulocytes [72].…”
Section: Recent Advances and Limitations In Clinical Applications Of ...mentioning
confidence: 99%
“…Raman spectroscopy, a label-free optical vibrational spectroscopy technique, has been widely used to quantitatively analyze molecular compositions of biological specimens and diagnosis of various human cancers ( 13–21 ). AI algorithms have been shown to improve the robustness of Raman spectroscopy-based precise cancer diagnosis ( 22 ). Particularly, previous studies have demonstrated the capability of Raman spectroscopy in intraoperative brain cancer detection ( 23–27 ).…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] AI algorithms improved the robustness of Raman spectroscopy for high-precision cancer diagnosis. [39] However, due to the weak spontaneous Raman signals, Raman spectroscopy-based cytology took up to 8 h for a complete analysis without spatial information. With remarkably boosted Raman signals, simulated Raman scattering (SRS) microscopy is a desirable method of label-free and high speed molecular imaging at the single cell level.…”
Section: Introductionmentioning
confidence: 99%